Proceedings of the 24th International Conference on World Wide Web 2015
DOI: 10.1145/2736277.2741639
|View full text |Cite
|
Sign up to set email alerts
|

Improving Paid Microtasks through Gamification and Adaptive Furtherance Incentives

Abstract: Crowdsourcing via paid microtasks has been successfully applied in a plethora of domains and tasks. Previous efforts for making such crowdsourcing more effective have considered aspects as diverse as task and workflow design, spam detection, quality control, and pricing models. Our work expands upon such efforts by examining the potential of adding gamification to microtask interfaces as a means of improving both worker engagement and effectiveness. We run a series of experiments in image labeling, one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…There is a large body of research in the crowdsourcing community studying optimal pricing strategies (Archak, 2010;Singer & Mittal, 2013) or the interplay between incentives and other factors such as existing social structures (relevant, for instance, when a crowdsourcing project is carried out in an existing social network or in an enterprise) or motivation. Studies such as (Feyisetan, Simperl, van Kleek, & Shadbolt, 2015;Kaufmann, Schulze, & Veit, 2011) have shown that contributors to crowdsourcing platforms are driven by a rich set of reasons and that relying on financial incentives only might miss great opportunities for engagement and performance gains.…”
Section: Liber Quarterly Volume 25 Issue 1 2015mentioning
confidence: 99%
“…There is a large body of research in the crowdsourcing community studying optimal pricing strategies (Archak, 2010;Singer & Mittal, 2013) or the interplay between incentives and other factors such as existing social structures (relevant, for instance, when a crowdsourcing project is carried out in an existing social network or in an enterprise) or motivation. Studies such as (Feyisetan, Simperl, van Kleek, & Shadbolt, 2015;Kaufmann, Schulze, & Veit, 2011) have shown that contributors to crowdsourcing platforms are driven by a rich set of reasons and that relying on financial incentives only might miss great opportunities for engagement and performance gains.…”
Section: Liber Quarterly Volume 25 Issue 1 2015mentioning
confidence: 99%
“…Designing tasks that induce curiosity is a task-agnostic strategy to improve worker retention [Law et al 2016]. Feyisetan et al [2015] propose a model to predict optimal combinations of financial and gamified incentives.…”
Section: Improve Intrinsic Motivationmentioning
confidence: 99%
“…Gamification has also been used in crowdsourcing [39]. In [19], authors have proposed a game called Wordsmith. Wordsmith is a single player game in which players attend in an image labeling task.…”
Section: Online Crowdsourcing Gamesmentioning
confidence: 99%